2021
DOI: 10.3389/fnut.2021.742081
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Phase Angle and Sarcopenia in Patients Undergoing Peritoneal Dialysis

Abstract: Introduction: There is limited data on the association between phase angle (PhA) and sarcopenia using both muscle strength and muscle mass in patients undergoing peritoneal dialysis (PD). We aimed to evaluate the association between PhA and sarcopenia in patients undergoing PD.Methods: We enrolled prevalent patients undergoing PD (n = 200). The patients were divided into tertiles based on their PhA level: low (n = 66; 1.9–4°), middle (n = 68; 4.1–4.9°), and high tertiles (n = 66; 5–8°). PhA was measured by a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
(58 reference statements)
0
25
1
1
Order By: Relevance
“…The studies were published between 2014 and 2022 and varied in sample size (33 to 645 patients). Among the included studies, twenty-one studies were conducted in Asian countries (China, Iran, Japan, Korea, Taiwan, Thailand, and Turkey) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], nine in European countries (France, Sweden, Spain, and United Kingdom) [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], eight in South American countries (Brazil and Argentina) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], two in the USA [ 57 , 58 ], and the remaining one in Australia [ 59 ]. These studies yielded a total sample of five continents (Asia: 45.6%, Europe: 25.9%, North America: 14.3%, South America: 13.7%, and Australia: 0.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 2014 and 2022 and varied in sample size (33 to 645 patients). Among the included studies, twenty-one studies were conducted in Asian countries (China, Iran, Japan, Korea, Taiwan, Thailand, and Turkey) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], nine in European countries (France, Sweden, Spain, and United Kingdom) [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], eight in South American countries (Brazil and Argentina) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], two in the USA [ 57 , 58 ], and the remaining one in Australia [ 59 ]. These studies yielded a total sample of five continents (Asia: 45.6%, Europe: 25.9%, North America: 14.3%, South America: 13.7%, and Australia: 0.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Another important result in this study is the inverse association between the phase angle and volume status. Previous studies have shown an association between phase angle and prognosis, including nutritional status and mortality in dialysis patients ( 28 , 29 ). The phase angle is originally associated with cellularity and water content to cell mass, and a high phase angle reveals high cellularity and low extracellular water to intracellular water ratio ( 30 ).…”
Section: Discussionmentioning
confidence: 95%
“…Han B et al[20] enrolled 80 patients undergoing PD showed that PhA correlated to serum albumin and lean tissue index (LTI) from bioimpedance. Recently, research including 200 patients with PD [21] demonstrated that PhA is independently associated with muscle mass, strength, and sarcopenia, but they used DXA to measure body composition. Whereas, in 2020, Pessoa et al illustrated that PhA had no association with sarcopenia, SMI, HGS, and walk speed in the old women[22].…”
Section: Discussionmentioning
confidence: 99%
“…Kosoku et al demonstrated a value of≤4.46 in kidney transplant patients, with a sensitivity of 74% and specificity of 70%[30]. Recently, a study about peritoneal dialysis without peritoneal dialysis fluid showed the cut-off value was≤4.4°(sensitivity 81.3%, specificity 59.6%)[21]. This may be since the total average age of our central dialysis patients(51.3±12.43 year) are lower than that of the patients included in the study (55.5±12.2 year).…”
Section: Discussionmentioning
confidence: 99%